HUNTING EL CHAPO : TAKING DOWN THE WORLD'S MOST WANTED DRUG LORD - Hogan, Andrew (DEA agent); Century, Douglas,|eauthor. (London : HarperCollinsPublishers, 2019)
This is the untold story of the American federal agent who captured the world's most-wanted drug-lord. This is the incredible story of Hogan's seven-year-long chase to capture El Chapo, a multibillionaire drug-lord and escape-artist posing as a Mexican Robin Hood, who in reality was a brutal sociopath responsible for the murders of thousands. His greedy campaign to take over his rivals' territories resulted in an unprecedented war with a body count of over 100,000.
Originally published: London: HarperCollinsPublishers, 2018.
Includes bibliographical references and index.
Keywords: Chapo, -- 1957-; Hogan, Andrew -- (DEA agent); Drug traffic -- Investigation -- Mexico; Undercover operations -- Mexico